EDEN ISS - Vrakking, Vincent; Bunchek, Jess; Schubert, Daniel; Zabel, Paul; Zeidler, Conrad; Dorn, Markus; Ferl, Robert; Paul, Anna-Lisa (2022)
Ant-Land Status Report describing activities and preliminary results of the 2021 Antarctic winter season and the 2021/22 Antarctic summer season